Tuning the ferrous coordination structure enables a highly reversible Fe anode for long-life all-iron flow batteries. Issue 46 (22nd November 2021) - Song, Yuxi; Zhang, Kaiyue; Li, Xiangrong; Yan, Chuanwei; Liu, Qinghua; Tang, Ao
Abstract : By effectively tuning the ferrous coordination structure that realizes a highly reversible Fe plating/stripping reaction at the anode, the all-iron RFB delivers an averaged 100% CE for 300 charge–discharge cycles. Abstract : An aqueous all-iron flow battery is a promising alternative for large-scale energy storage applications due to its low cost and high safety. However, the inferior Fe plating/stripping reversibility and hydrolysis of Fe 2+ at the anode significantly limit its capacity retention and lifespan. Herein, we propose a coordination strategy to delicately tune the coordination structure of Fe 2+, enabling effective suppression of Fe 2+ hydrolysis and a highly reversible Fe plating/stripping reaction. Firstly, citrate is screened to feature a strong ligand field with the largest splitting energy among various ligand anions. Subsequently, sodium citrate bearing a high LUMO and large binding energy is identified to be the most suitable additive for the anolyte. By adding sodium citrate into FeCl2, the formation of a highly stable Fe 2+ –citrate coordination structure is confirmed via carboxyl groups. This effectively alters the intrinsic [Fe(H2 O)6 ] 2+ structure and yields remarkably improved Fe deposition during charging, allowing a highly reversible Fe plating/stripping reaction at the anode. Finally, the all-iron flow cell adopting Fe 2+ –citrate anolyte delivers an averaged 100% CE for 300 charge–discharge cycles without capacity decay, which is the longest cycle-life reported in the open literature.